Method for overcoming strip-shaped defects on surface of cold-rolled coil

By adjusting the composition and process parameters of low-carbon steel materials, the strip defect problem of cold-rolled coil surface is solved, the hardness and density of the material are improved, the generation and adhesion of iron oxide sheet is reduced, and cold rolling without strip defects is achieved Roll surface.

CN119216382APending Publication Date: 2024-12-31SHANGHAI MEISHAN IRON & STEEL CO LTD

Patent Information

Application Number
CN202310783464.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The surface of low-carbon cold-rolled coils has strip defects, which are mainly caused by the pressing of the iron oxide sheet during hot rolling, which is difficult to effectively solve the problem in the existing technology.

Method used

By adjusting the material composition and process parameters, establish the relationship between material hardness and carbon equivalent, control the hot rolling furnace temperature, laminar cooling water volume and coiling temperature, improve the hardness and density of the material, and reduce the generation and adhesion of iron oxide sheets. Specific steps include: adjusting the carbon and manganese content, controlling the oven temperature to 1200±20℃, increasing the laminar cooling water volume, and reducing the winding temperature to 620±20℃, ensuring that the improved material hardness is between 94-98HRB.

Benefits of technology

It effectively improves the hardness and density of low-carbon steel materials, reduces the generation and adhesion of iron oxide sheets, avoids the occurrence of strip-like defects on the surface of cold-rolled coils, and meets the requirements of material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a method for solving strip-shaped defects on the surface of a cold-rolled coil. The method comprises the steps of redesigning components and hardness of a product, adjusting the hot rolling tapping temperature, increasing the cooling water amount during laminar cooling after hot rolling, reducing the coiling temperature and the like. According to the method for solving the strip-shaped defects on the surface of the cold-rolled coil, the hardness of a low-carbon steel material is improved, the compactness of a material structure is improved, oxide scale cannot be pressed into the surface of the hot-rolled coil, the slab heating tapping temperature is reduced, the coiling temperature of the hot-rolled coil is reduced, and therefore the problem that the oxide scale of the hot-rolled coil is pressed in is solved; and strip-shaped defects cannot be generated when the hot-rolled coil is further cold-rolled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for solving strip defects on the surface of a cold-rolled coil, and belongs to the technical field of metal smelting. Background Art

[0002] Strip defects appeared on the surface of low-carbon cold-rolled coils. After sampling and analysis, it was found that it was caused by the intrusion of iron oxide scale during hot rolling, which turned into strip defects during cold rolling. Therefore, the essence of this defect is the intrusion of iron oxide scale during hot rolling.

[0003] There are two aspects of the formation of strip-shaped iron scale on the surface of cold-rolled coils. One is the primary iron scale produced when the slab is heated in the furnace, and the other is the secondary iron scale produced during finishing rolling, laminar cooling and coiling. The primary iron scale is a rolling-pressed iron scale during the hot rolling process, and the strip-shaped iron scale defect is formed due to rolling elongation; the secondary iron scale is formed during finishing rolling, laminar cooling and coiling, and sometimes cannot be washed away by pickling before cold rolling, which will cause strip-shaped defects in the cold-rolled coil.

[0004] For the scale defects of hot-rolled coils or cold-rolled coils, the existing methods to solve the problem are either to use "water explosion" (such as patent No. CN85108549) or "spray" (such as patent No. CN01805403X) to blow away the scale on the surface of the coil. Or use the "crushing" method (such as patent No. CN2016107446883) to crush the high-temperature ferrous oxide to solve the problem of scale pressing. Or use the hot rolling sparse cooling method (such as patent No. CN200710202402X). Summary of the invention

[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the above-mentioned technology and provide a method for improving the hardness of low-carbon steel materials and improving the density of material structure so that iron oxide scale is not pressed into the surface of hot-rolled coils to solve the strip defects on the surface of cold-rolled coils.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: a method for solving the strip defects on the surface of cold-rolled coils, comprising the following steps: (1) Establish the relationship between material hardness H and material carbon equivalent CEV: CEV1 / CEV2=H1 / H2; where CEV1 and CEV2 are the material carbon equivalent of the product before improvement and the material carbon equivalent of the product after improvement, respectively; H1 and H2 are the material hardness of the product before improvement and the material hardness of the product after improvement, respectively; The definition of the carbon equivalent CEV of a material is: CEV=C+Mn / 6, where C and Mn are the percentages of carbon and manganese in the material, respectively; The hardness of the improved product is 94-98HRB; (2) During hot rolling, the furnace temperature is controlled to be 1200±20℃; (3) Increase the cooling water volume during laminar cooling after hot rolling; (4) After laminar cooling of the hot coil, reduce the coiling temperature to 620±20℃.

[0007] A further improvement of the above scheme is that: in the steps (3) and (4), the relationship between the coiling temperature and the laminar cooling amount before and after the improvement is: T1 / T2=2*M1 / M2, where: T1 is the coiling temperature before the improvement, M1 is the number of laminar cooling water nozzles before the improvement; T2 is the coiling temperature after the improvement, and M2 is the number of laminar cooling water nozzles after the improvement.

[0008] The method for solving the strip defects on the surface of the cold-rolled coil provided by the present invention improves the hardness of the low-carbon steel material and improves the density of the material structure, so that the iron oxide scale is not pressed into the surface of the hot-rolled coil, the slab heating furnace temperature is reduced, and the hot-rolled coil winding temperature is reduced, thereby solving the problem of the iron oxide scale being pressed into the hot-rolled coil, so that the hot-rolled coil will not produce strip defects when further cold-rolled. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a grain photograph of a defective coil before the present invention is applied.

[0010] Figure 2 This is a grain photo of the coil of Case 5.

[0011] Figure 3 This is a surface photograph of a defective coil before the present invention was applied.

[0012] Figure 4 This is a photo of the coil surface of Case 5. Implementation

[0013] Before the method for solving the strip defects on the surface of cold-rolled coils of this embodiment is applied, the composition and related properties of the existing unimproved low-carbon steel products are as follows: C: 0.02%-0.035%, Si: ≤0.03%, Mn: 0.15%-0.25%, P: ≤0.014%, S: ≤0.012%, Al: 0.025%-0.05%, N: ≤0.0035%, and the rest are unavoidable impurity elements; average hardness (Rockwell) 92HRB.

[0014] The method for solving the strip defects on the surface of the cold-rolled coil in this embodiment comprises the following steps: (1) Establish the relationship between material hardness H and material carbon equivalent CEV: CEV1 / CEV2=H1 / H2; where CEV1 and CEV2 are the material carbon equivalent of the product before improvement and the material carbon equivalent of the product after improvement, respectively; H1 and H2 are the material hardness of the product before improvement and the material hardness of the product after improvement, respectively; The definition of the carbon equivalent CEV of a material is: CEV=C+Mn / 6, where C and Mn are the percentages of carbon and manganese in the material, respectively; The manganese content in the product cannot be too high. In consideration of increasing the carbon content, the manganese content must be appropriately reduced. Otherwise, the hardness and yield strength of the low carbon steel will increase significantly, and the performance and quality requirements of the product cannot be met. Therefore, the manganese content of the low carbon steel is fine-tuned on the original basis. According to user requirements, it is controlled within 0.10%-0.30%. Before the improvement, it was controlled at 0.15%-0.25%, and after the improvement, it was reduced to 0.13%-0.21%.

[0015] Therefore, according to the established proportional relationship between carbon equivalent and hardness, the carbon equivalent formula and the original composition, hardness, and the designed manganese composition and hardness value listed above, the improved carbon content range can be calculated. The improved carbon content range is between 0.025% and 0.045%, but considering that the hardness and yield strength of the product cannot be too large, the lower limit is corrected to 0.024%, so the improved carbon content design range is 0.024%-0.045%. Except for the changes in carbon and manganese, the other components remain unchanged. In this way, the chemical composition of the improved product is as follows: C: 0.024%-0.045%, Si: ≤0.03%, Mn: 0.13%-0.21%, P: ≤0.014%, S: ≤0.012%, Al: 0.025%-0.05%, N: ≤0.0035%, and the rest are unavoidable impurity elements.

[0016] As for the hardness design of the product, increasing the hardness of the product will reduce or eliminate the intrusion of iron oxide, but if the hardness of the product is too high, it will cause the elongation of the product to decrease, and the user will cause the product to crack when processing and deforming. Therefore, the hardness of low-carbon steel products cannot be increased too much, and can only be adjusted within a relatively narrow range. Under normal circumstances, the adjustment range of low-carbon steel hardness is preferably 2-6HRB (Rockwell hardness, the same below). The average hardness before the improvement is 92HRB, so after the improvement, its hardness is planned to be 94-98HRB, with an average of 96HRB.

[0017] (2) During hot rolling, the furnace temperature is controlled to be slightly lowered to reduce the amount of iron oxide scale produced in the slab as much as possible, thereby avoiding the pressing of more iron oxide scale during hot rolling. When the furnace temperature is high, the number of oxygen atoms decomposed into oxygen molecules in the furnace is large, and the movement speed of iron atoms in the slab increases, resulting in more iron oxide formed by the combination of oxygen atoms and iron atoms, which is manifested as a thickening of the iron oxide scale. When the furnace heating temperature is reduced, the amount of iron oxide produced is reduced, which is manifested as a thinning of the iron oxide scale. According to experiments, when the furnace temperature is reduced from the original 1220±20℃ to 1200±20℃, the thickness of the iron oxide scale can be effectively reduced, and at this heating temperature, the strip-shaped iron oxide scale of the coil can be solved.

[0018] (3) Control the cooling water volume during laminar cooling after hot rolling to improve the grain fineness of the coil. First, it reduces the generation of iron oxide scale, and second, it further ensures the hardness of the coil surface, making it difficult for iron oxide scale to adhere to the coil surface. When the laminar cooling volume is doubled, the grain size of the coil material will increase by 1.0-1.5 levels, that is, from the original 7.0 level to 7.5-8.5 levels.

[0019] The mechanism of laminar cooling in refining the grains of hot rolled coils, reducing iron oxide scale and improving hardness: the laminar cooling intensity increases, which can prevent the grains in the material from growing, making the grains finer, thereby achieving the purpose of refining the grains and improving the grain grade. After the material grains are refined, the density of the material is improved, making the material less likely to oxidize (oxygen atoms are not easy to penetrate), thereby reducing the generation of iron oxide scale. In addition, increasing the amount of laminar cooling will increase the cementite in the material structure, thereby increasing the hardness of the material.

[0020] (4) After laminar cooling of the hot coil, the coiling temperature is lowered to further improve the grain fineness of the coil. First, the generation of iron oxide scale is further reduced; second, the hardness of the coil surface is further ensured, so that the iron oxide scale is not easy to adhere to the coil surface. Third, when the coil is pickled before subsequent cold rolling, the grain fineness of the coil is high and the strip surface is dense due to the previous laminar cooling and hot rolling coil temperature control. Therefore, a small amount of iron oxide scale that may be missed in the dense layer on the coil surface is easy to pickle. In this way, the pressure of iron oxide scale during subsequent cold rolling is reduced or even eliminated. According to experiments, when the coiling temperature of the hot rolled coil is reduced from the original 680±20℃ to 620±20℃, the above three purposes can be achieved.

[0021] In step (3) and step (4), the relationship between the coiling temperature and the laminar cooling amount before and after the improvement is: T1 / T2=2*M1 / M2, where: T1 is the coiling temperature before the improvement, M1 is the number of laminar cooling water nozzles before the improvement; T2 is the coiling temperature after the improvement, and M2 is the number of laminar cooling water nozzles after the improvement. The specific design situation is as follows: The mechanism of lowering the coiling temperature to improve the grain size, hardness and reduce the scale of iron oxide: After lowering the coiling temperature, the kinetic conditions for promoting the growth of grains in the material are insufficient, thereby preventing the growth of grains and improving the grain size of the material. After lowering the coiling temperature, the cementite in the material structure will increase, increasing the hardness of the material. After lowering the coiling temperature, due to the increase in the grain size of the material, the material structure is dense, oxygen atoms are not easy to penetrate into the material, and the generation of scale of iron oxide is reduced.

[0022] Five implementation cases are listed below to illustrate the effects of the improvements.

[0023] Step 1: Composition design and actual hardness. See Table 1: Table 1. Ingredient Examples (Unit: %) C Si Mn P S Al N The present invention 0.024-0.045 ≤0.03 0.13-0.21 ≤0.014 ≤0.012 0.025-0.05 ≤0.0035 Case 1 0.032 0.008 0.184 0.012 0.008 0.030 0.0019 Case 2 0.038 0.006 0.163 0.011 0.009 0.037 0.0022 Case 3 0.033 0.004 0.164 0.010 0.008 0.029 0.0026 Case 4 0.034 0.006 0.176 0.012 0.009 0.028 0.0028 Case 5 0.036 0.008 0.168 0.012 0.009 0.032 0.0031 Existing patents 0.06~0.12 ≤0.30 1.05~1.25 ≤0.025 ≤0.015 - - Step 2: The furnace temperature, number of laminar cooling water spray valves opened, coiling temperature, material hardness and grain size grade are shown in Table 2.

[0024] Table 2. Hot rolling related parameters, material hardness and grain size grade Oven temperature (℃) Number of laminar cooling water spray valves opened Coiling temperature (℃) Cold rolled material hardness (Rockwell HRB) Hot coil grain size grade The present invention 1190-1210 50-60 600-640 94-98 7.5-8.5 Case 1 1197 53 635 95.9 7.5 Case 2 1200 58 615 96.7 8.0 Case 3 1205 55 628 95.2 7.5 Case 4 1199 60 619 96.3 8.0 Case 5 1201 59 621 95.9 8.0 Before improvement 1225 30 680 92 7.0 Existing patents Unknown Not this design 500~520 Unknown Unknown It can be seen from Table 2 that after lowering the furnace temperature, increasing the laminar cooling amount and lowering the coiling temperature, the grain size of the coil material increased from the original 7.0 to 7.5-8.0. In addition, after the coiling temperature was lowered, no strip-shaped iron oxide scale defects appeared during pickling.

[0025] Step 3: Comparison of material properties before and after improvement, see Table 3.

[0026] Table 3. Comparison of hot rolled coil performance before and after improvement Hot rolled coil yield strength (MPa) Hot rolled coil tensile strength (MPa) Hot coil elongation (%) Hot coil grain size grade Cold roll hardness (Rockwell HRB) Before improvement (mean) 220.5 306.5 49.7 7.0 91.7 After improvement (mean) 248 331.5 40.5 8.0 95.9 standard ≥200 ≥300 ≥35 - - It can be seen from Table 3 that the performance after improvement meets the requirements, the grain size grade is one level higher than before improvement, and the hardness of the cold-rolled coil is improved to the expected target (the expected design average hardness is 96HRB) than before improvement.

[0027] Step 4: Evaluation of the effect after improvement. After the improvement, the hardness of the cold-rolled coil reaches the expected design value, the grain size grade is improved by one level, and the performance does not fluctuate greatly, meeting the existing requirements. After production testing, the strip defects on the surface of the cold-rolled coil disappeared after the improvement. Reference Figure 1 and Figure 2 , Figure 1 is a grain photo of a defective coil in the database before the present invention is applied, Figure 2 This is a photo of the coil grains in Case 5; the grains were large before improvement and became smaller after improvement.

[0028] refer to Figure 3 and Figure 4 , Figure 3 is a surface photo of a defective coil in the database before the present invention is applied. Figure 4 This is a photo of the coil surface of Case 5; after applying the present invention, the coil surface is smooth and has no strip defects.

[0029] It can be seen from the actual solution of the problem that the present invention can effectively solve the strip defects on the surface of the cold-rolled coil. The idea based on "the ratio of the carbon equivalent before and after the improvement is equal to the ratio of the hardness before and after the improvement" can effectively determine the carbon content of the material and improve the hardness of the material.

[0030] The present invention is not limited to the above embodiments. Any technical solution formed by equivalent replacement falls within the protection scope required by the present invention.

Claims

1. A method for solving strip defects on the surface of cold-rolled coils, characterized in that: The steps include: (1) Establish the relationship between material hardness H and material carbon equivalent CEV: CEV1 / CEV2=H1 / H2; where CEV1 and CEV2 are the material carbon equivalent of the product before improvement and the material carbon equivalent of the product after improvement, respectively; H1 and H2 are the material hardness of the product before improvement and the material hardness of the product after improvement, respectively; The definition of the carbon equivalent CEV of a material is: CEV=C+Mn / 6, where C and Mn are the percentages of carbon and manganese in the material, respectively; The hardness of the improved product is 94-98HRB; (2) During hot rolling, the furnace temperature is controlled to be 1200±20℃; (3) Increase the cooling water volume during laminar cooling after hot rolling; (4) After laminar cooling of the hot coil, reduce the coiling temperature to 620±20℃.

2. The method for solving the strip defects on the surface of cold-rolled coil according to claim 1, characterized in that: In the steps (3) and (4), the relationship between the coiling temperature and the laminar cooling amount before and after the improvement is: T1 / T2=2*M1 / M2, where: T1 is the coiling temperature before the improvement, M1 is the number of laminar cooling water nozzles before the improvement; T2 is the coiling temperature after the improvement, and M2 is the number of laminar cooling water nozzles after the improvement.

Citation Information

Patent Citations

  • Hot rolled steel plate surface oxidation iron sheet control method for vanadium-containing automobile beam

    CN101147920A

  • Cold rolling hot-dip steel with thickness greater than 1.5 mm for folding forming and production method thereof

    CN103451519A

  • Cold-rolled martensite steel plate with yield strength of 750 MPa grade and manufacturing method thereof

    CN107619993A

  • Low-carbon steel coil plate for oil filter thread cover plate and manufacturing method thereof

    CN110184538A

  • Control method of hot rolled plate surface oxidized iron powder

    CN110899331A

Cited By

  • Device for improving strip-shaped defects on lower surface of aluminum alloy strip and working method

    CN119819731A

  • An apparatus and working method for improving strip defects on the lower surface of an aluminum alloy strip

    CN119819731B

  • Device for improving strip-shaped defects on lower surface of aluminum alloy strip

    CN223718020U